HUBUNGAN ANTARA DUKUNGAN KELUARGA TERHADAP KEPATUHAN PEMBATASAN MAKANAN TINGGI KALIUM PADA PASIEN GAGAL GINJAL KRONIS YANG MENJALANI HEMODIALISA DI RSUD CIAMIS - Risnawati Risnawati; Rosmiati Rosmiati; Nur Hidayat (LPPM STIKes Muhammadiyah Ciamis, 2020)
Background: Chronic renal failure is a clinical syndrome caused by chronic, progressive and irreversible decline in kidney function. Impaired kidney function occurs when the body fails to maintain metabolism, fluid and electrolyte balance, causing retention of urea and other nitrogenous waste in the blood. This damage causes problems in the ability and strength of the body that causes disrupted work activities, the body easily tired and weak so that the quality of life decreases. Hemodialysis is the therapy most often used as a kidney replacement. In addition to undergoing hemodialysis, patients are required to restrict eating, including high-potassium foods. To improve compliance, support from the family is needed to play arole in providing supervision and support.Purpose: To determine the correlation between family support for potassium food restriction compliance in patients with chronic renal failure undergoing hemodialysis in RSUD Ciamis.The Method: Quantitative analytic uses questionnaire and interview with cross sectional study design on 62 respondents from a population of 177 people using simple random sampling technique taken from all patients with chronic kidney failure who undergo hemodialysis in RSUD Ciamis.Results: The statistical test results using the Chi-Square test obtained p value 0,000 , meaning that there is a significant correlation between family support for potassium food restriction compliance rates in patients with chronic renal failure undergoing hemodialysis.Discus: Good family support felt by patients will determine the level of compliance because they feel cared for.Conclusion: There is a significant correlation between family support for potassium food restriction compliancein patients with chronic renal failure undergoing hemodialysis in RSUD Ciamis.